A GALS Approach for Programming Distributed Interactive Multimedia Applications - Santos, Rodrigo C. M.; Sant’Anna, Francisco; Rodriguez, Noemi (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
Multi-device (or distributed) multimedia applications are programs designed for exploring multiple devices during their execution. Most of these applications allow users to interact with them, defining their flow of execution. We argue that current programming approches still lack proper support for developing these applications. In a previous work we have discussed the use of the synchronous language Céu for programming multimedia, which has led to the development of the library Céu-Media as a partial result of this work. Now we are extending our work for approaching distributed applications. More precisely, we are devising a GALS (Globally Asynchronous Locally Synchronous) middleware that supports the development and execution of multi-device multimedia applications and guarantees the consistency between devices.